Polyester film for surface protective film of flexible display

A biaxially stretched polyester film with a hard coat layer addresses the lack of pencil hardness in flexible displays, offering enhanced scratch and impact resistance for curved surfaces.

JP2024178357AActive Publication Date: 2024-12-24TOYOBO CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024165240
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-24
Estimated Expiration
2038-07-20

AI Technical Summary

Technical Problem

Existing transparent films used in flexible displays lack sufficient pencil hardness and are either expensive or have issues with scratch resistance, making them unsuitable for protecting curved surfaces in flexible displays.

Method used

A biaxially stretched polyester film with a thickness of 25 to 100 μm and an indentation depth of 1.4 μm or less, featuring a plane orientation coefficient ΔP of 0.160 or more, and an easily adhesive layer, when laminated with a hard coat layer, enhances surface hardness and impact resistance.

Benefits of technology

The film provides high pencil hardness, preventing scratches and impact on flexible displays, ensuring durability and maintaining excellent design aesthetics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178357000001
    Figure 2024178357000001
Patent Text Reader

Abstract

To inexpensively provide a polyester film showing a high pencil hardness scale when a hard coat layer is laminated.SOLUTION: A polyester film for a surface protective film of a flexible display is provided, which has a thickness of 25 to 100 μm and an indentation depth of 1.4 μm or less after a test load is removed. A hard coat film for a surface protective film of a flexible display and a display body are provided, which use the above polyester film for a surface protective film of a flexible display.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyester film, and to a polyester film which can provide high pencil hardness when a hard coat layer or the like is laminated thereon. [Background technology]

[0002] Displays and mobile terminal devices such as smartphones are becoming thinner and lighter. Currently, both use rigid housings, so tempered glass is generally used to protect the display. However, displays that emphasize design are becoming more popular in recent years. For example, displays with special shapes such as circular shapes are popular. In particular, there has been a demand for bendable displays in order to install them on curved surfaces.

[0003] However, since glass materials cannot be used for flexible displays, acrylic sheets and the like have been used, but thin acrylic sheets have problems with being vulnerable to scratches and impacts. Polycarbonate, which is resistant to impacts and has high light resistance, is sometimes used, but it is expensive and has problems with low pencil hardness. On the other hand, polyester films are inexpensive and have excellent impact resistance, but have problems with insufficient pencil hardness.

[0004] To achieve these goals, Patent Document 1 proposes a material with high hardness and flexibility as a hard coat material. However, the material is expensive and has problems with versatility, as well as low scratch resistance of the surface.

[0005] Also, a transparent polyimide material that can achieve high pencil hardness without relying on a hard coat material has been proposed, as in Patent Document 2. However, this material is very expensive and has problems with mass production. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2017-008148 A [Patent Document 2] JP 2016-222797 A Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention is intended to solve the problems associated with transparent films as described above, and aims to provide an inexpensive polyester film that exhibits high pencil hardness when a hard coat layer is laminated thereon. [Means for solving the problem]

[0008] That is, the present invention comprises the following: 1. A polyester film for surface protection of flexible displays, with a thickness of 25 to 100 μm and a penetration depth of 1.4 μm or less after the test force is removed. 2. The polyester film for surface protection of a flexible display as described in 1 above, having a plane orientation coefficient ΔP of 0.160 or more. 3. A polyester film for surface protection of a flexible display as described in claim 1 or 2, which is a biaxially oriented polyester film and has an easy-adhesion layer on at least one surface of the biaxially oriented polyester film. 4. A hard coat film for surface protection of flexible displays, comprising the polyester film for surface protection of flexible displays according to any one of the above 1 to 3, and a hard coat layer on at least one surface of the polyester film for surface protection of flexible displays. 5. A display using the hard coat film for surface protection of a flexible display described in 4 above as a surface protection film. Effect of the Invention

[0009] The polyester film of the present invention, when laminated with a hard coat layer, has a higher surface hardness than a general polyester film, and the hard coat film is used as a surface protection film for a display body, making it possible to provide a display body that is resistant to scratches, impacts, deformation, etc. on the surface of the display body and has excellent design. The display body can provide beautiful images. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] (Display body) The display body in the present invention generally refers to a display device, and the types of displays include LCD, organic EL display, inorganic EL display, LED, FED, etc., but LCD, organic EL, and inorganic EL, which have a foldable structure, are preferred. In particular, organic EL, which has a reduced layer structure and a wide color gamut, is more preferred.

[0011] The display body may take any form, including a large screen, display, digital signage, bendable mobile terminal, and PC, and may be used without limitation. In particular, it is preferable to use it in a display with a touch panel that has a touch panel function that allows direct touch operation, digital signage, bendable mobile terminal, PC, and the like. It is particularly preferable that the display body is a flexible display as described below.

[0012] (Flexible Display) Flexible displays are continuous displays that can be bent according to the application, and are preferably thin and lightweight at the same time. In particular, foldable displays, which are bendable displays, rollable displays, which are rollable displays, and displays that can be used like paper are examples of such displays.

[0013] (Polyester film) Transparent films include films with high light transmittance and low haze, such as PI film, polyester film, polycarbonate film, acrylic film, TAC film, and cycloolefin polymer film. Among these, polyester film, which has high impact resistance and appropriate pencil hardness, is preferred, and polyethylene terephthalate film, which can be produced inexpensively, is particularly preferred.

[0014] In the present invention, the polyester film may be a single-layer film made of one or more polyester resins, or when two or more types of polyester are used, it may be a multilayer film or an ultra-multilayer laminate film having a repeating structure.

[0015] Examples of polyester resins include polyester films made of polyethylene terephthalate, polybutylene terephthalate, polyethylene-2,6-naphthalate, or copolymers mainly composed of these resin components. Among these, biaxially stretched polyethylene terephthalate films are particularly preferred in terms of mechanical properties, heat resistance, transparency, price, etc.

[0016] When a polyester copolymer is used for the base film, examples of the dicarboxylic acid component of the polyester include aliphatic dicarboxylic acids such as adipic acid and sebacic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalenedicarboxylic acid; and polyfunctional carboxylic acids such as trimellitic acid and pyromellitic acid. Examples of the glycol component include fatty acid glycols such as ethylene glycol, diethylene glycol, 1,4-butanediol, propylene glycol, and neopentyl glycol; aromatic glycols such as p-xylene glycol; alicyclic glycols such as 1,4-cyclohexanedimethanol; and polyethylene glycols having an average molecular weight of 150 to 20,000. The mass ratio of the copolymerization components of the preferred copolymer is less than 20% by mass. When it is less than 20% by mass, the film strength, transparency, and heat resistance are maintained, which is preferable.

[0017] In addition, in the production of polyester films, the intrinsic viscosity of at least one type of resin pellet is preferably in the range of 0.50 to 1.0 dl / g. If the intrinsic viscosity is 0.55 dl / g or more, the pencil hardness after hard-coating is improved, which is preferable. More preferably, it is 0.58 dl / g or more, and particularly preferably, it is 0.63 dl / g or more. On the other hand, if the intrinsic viscosity is 1.00 dl / g or less, the increase in filtration pressure of the molten fluid is not too large, which is preferable since it is easy to operate the film production stably.

[0018] Regardless of whether the film is a single-layered or laminated film, the intrinsic viscosity of the film is preferably 0.50 dl / g or more. This is preferable because the molecular weight of the polyester resin increases, improving the elastic behavior of the film and effectively suppressing deformation against the load of the pencil during pencil hardness measurement. It is more preferably 0.55 dl / g or more, and particularly preferably 0.63 dl / g or more. On the other hand, although the pencil hardness is improved by increasing the intrinsic viscosity, there is a concern that the productivity may decrease, so an intrinsic viscosity of 1.00 dl / g or less is preferable because it allows for production with good operability.

[0019] The thickness of the polyester film is preferably 25 to 100 μm, and more preferably 30 to 75 μm. A thickness of 25 μm or more is preferable because of improved handling properties and impact resistance, while a thickness of 100 μm or less is advantageous for weight reduction and is also preferable because of excellent flexibility and processability.

[0020] The surface of the polyester film of the present invention may be smooth or uneven, but since it is used as a protective film for the surface of a display, it is not preferable for the optical properties to be deteriorated due to the unevenness. The haze is preferably 3% or less, more preferably 2% or less, and most preferably 1% or less. If the haze is 3% or less, the visibility of the image can be improved. The lower limit of the haze is preferably as small as possible, but it may be 0.1% or more, or 0.3% or more.

[0021] As mentioned above, in order to reduce haze, it is better for the unevenness of the film surface to be not too large. However, in order to provide a certain degree of slipperiness from the viewpoint of ease of handling, unevenness can be formed by blending a filler into the surface polyester resin layer or by coating a coat layer containing a filler during the film formation process.

[0022] The method of blending particles into the base film can be a known method. For example, it can be added at any stage of polyester production, but preferably it can be added as a slurry dispersed in ethylene glycol or the like at the stage of esterification, or after the completion of transesterification reaction and before the start of polycondensation reaction, and polycondensation reaction can be carried out. It can also be carried out by using a vented kneading extruder to blend the slurry of particles dispersed in ethylene glycol or water with polyester raw material, or by using a kneading extruder to blend dried particles with polyester raw material.

[0023] Among them, a method is preferred in which aggregated inorganic particles are homogeneously dispersed in a monomer liquid that will become a part of the polyester raw material, and then the filtered product is added to the remainder of the polyester raw material before, during, or after the esterification reaction. According to this method, since the monomer liquid has a low viscosity, homogeneous dispersion of the particles and highly accurate filtration of the slurry can be easily performed, and when added to the remainder of the raw material, the dispersibility of the particles is good and new aggregates are unlikely to be generated. From this viewpoint, it is particularly preferred to add to the remainder of the raw material in a low temperature state before the esterification reaction.

[0024] In addition, the number of protrusions on the film surface can be further reduced by a method in which, after obtaining a polyester containing particles in advance, the pellets are mixed and extruded with pellets not containing particles (master batch method).

[0025] The polyester film may contain various additives, such as antistatic agents, UV absorbers, and stabilizers, within a range that maintains the total light transmittance in a preferred range.

[0026] The total light transmittance of the polyester film is preferably 85% or more, and more preferably 87% or more. If the transmittance is 85% or more, visibility can be sufficiently ensured. Although it can be said that the higher the total light transmittance of the polyester film, the better, it may be 99% or less, or 97% or less.

[0027] The surface of the polyester film of the present invention may be subjected to a treatment for improving adhesion to a resin forming a hard coat layer or the like.

[0028] Examples of the surface treatment method include roughening treatment using sandblasting or solvent treatment, and oxidation treatment such as corona discharge treatment, electron beam irradiation treatment, plasma treatment, ozone or ultraviolet irradiation treatment, flame treatment, chromic acid treatment, or hot air treatment, and any of these methods can be used without any particular limitation.

[0029] In addition, the adhesion can be improved by an adhesion improving layer such as an easy-adhesion layer. The easy-adhesion layer can be made of any resin such as an acrylic resin, a polyester resin, a polyurethane resin, or a polyether resin, and can be formed by a general coating method, preferably a so-called in-line coating method.

[0030] The polyester film described above can be produced, for example, through a polymerization step in which inorganic particles are homogeneously dispersed in a monomer liquid that becomes a part of the polyester raw material, the dispersion is filtered, and then the dispersion is added to the remainder of the polyester raw material to polymerize the polyester, and a film formation step in which the polyester is melt-extruded through a filter into a sheet, which is cooled and stretched to form a base film.

[0031] Next, a method for producing a biaxially stretched polyester film will be described in detail using an example in which polyethylene terephthalate (hereinafter, sometimes referred to as PET) pellets are used as the raw material for the base film, but the present invention is not limited to this example. In addition, the number of layers, such as a single layer structure or a multilayer structure, is not limited.

[0032] After mixing and drying PET pellets in a predetermined ratio, the mixture is fed to a known melt lamination extruder, extruded from a slit die into a sheet, and cooled and solidified on a casting roll to form an unstretched film. In the case of a single layer, one extruder is sufficient, but in the case of producing a film with a multilayer structure, two or more extruders, two or more manifolds or merging blocks (e.g., merging blocks having a rectangular merging portion) are used to laminate multiple film layers constituting each outermost layer, and a sheet of two or more layers is extruded from a die and cooled on a casting roll to form an unstretched film.

[0033] In this case, it is preferable to perform high-precision filtration to remove foreign matter contained in the resin at any location where the molten resin is kept at about 280° C. during melt extrusion. The filter material used for high-precision filtration of the molten resin is not particularly limited, but a filter material made of sintered stainless steel is preferable because it has excellent performance in removing aggregates and high-melting organic matter mainly composed of Si, Ti, Sb, Ge, and Cu.

[0034] Furthermore, the filtration particle size (initial filtration efficiency 95%) of the filter medium is preferably 20 μm or less, particularly preferably 15 μm or less. If the filtration particle size (initial filtration efficiency 95%) of the filter medium exceeds 20 μm, foreign matter with a size of 20 μm or more cannot be sufficiently removed. By using a filter medium with a filtration particle size (initial filtration efficiency 95%) of 20 μm or less to perform high-precision filtration of molten resin, productivity may decrease, but it is preferable to obtain a film with few protrusions due to coarse particles.

[0035] Specifically, for example, PET pellets are thoroughly vacuum-dried, then fed to an extruder, melt-extruded into a sheet at about 280°C, and cooled and solidified to form an unstretched PET sheet. The unstretched sheet obtained is stretched 3.1 to 5.0 times in the longitudinal direction with a roll heated to 80 to 120°C to obtain a uniaxially oriented PET film. Furthermore, the end of the film is held by a clip and introduced into a hot air zone heated to 80 to 180°C, dried, and then stretched 2.5 to 5.0 times in the width direction. Subsequently, the film is introduced into a heat treatment zone at 160 to 250°C, where heat treatment is performed for 1 to 60 seconds to complete the crystal orientation. During this heat treatment process, a relaxation treatment of 1 to 12% may be performed in the width direction or longitudinal direction as necessary.

[0036] (Crystallization degree) The degree of crystallinity is mainly determined by the amount of heat applied to the film in the heat treatment zone. The amount of heat is determined by various conditions such as film-forming equipment conditions, film-forming speed, and film thickness, so the degree of crystallinity is not determined only by the heat treatment temperature. However, the heat treatment temperature is preferably 160 to 250°C, and more preferably 200 to 240°C. A heat treatment temperature of 160°C or higher is preferable because it can promote crystallization. A heat treatment temperature of 250°C or lower is preferable because it can suppress a decrease in crystallization due to remelting of the polyester.

[0037] In order to ensure sufficient pencil hardness after hard coating, the crystallinity of the film measured by the density method is preferably 48% or more, and the crystallinity of the film surface measured by the ATR method is preferably 1.20 or more.

[0038] The crystallinity of the polyester film measured by the density method is preferably 48% or more, more preferably 50% or more, and even more preferably 52% or more. Although a high crystallinity is preferable, the upper limit of the film that can be produced is about 65%.

[0039] The crystallinity of the film surface measured by the ATR method is preferably 1.20 or more, more preferably 1.25 or more, and even more preferably 1.27 or more. It is preferable that the crystallinity of the film surface measured by the ATR method is high, but the upper limit of the film that can be produced is about 3.0.

[0040] The indentation depth in the film thickness direction after the test force is removed using a dynamic ultra-microhardness tester is preferably 1.4 μm or less, more preferably 1.35 μm or less, and even more preferably 1.30 μm or less. By lowering the indentation depth after the test force is removed (final deformation amount under load), deformation after pencil hardness evaluation can be suppressed, and the pencil hardness can be improved.

[0041] Planar orientation ΔP is preferably 0.160 or more, more preferably 0.163 or more, and even more preferably 0.165 or more. By increasing the planar orientation, the film becomes stronger against the load in the thickness direction, and the deformation amount at the time of unloading can be suppressed. Although it is preferable that the plane orientation is high, the upper limit of the film that can be formed is about 0.170.

[0042] The areal stretching ratio is preferably 12.5 times or more, more preferably 13 times or more, and further preferably 14 times or more. By increasing the areal stretching ratio, the orientation in the plane direction of the film can be strengthened, and ΔP can be increased.

[0043] The stretching method is not particularly limited and may be simultaneous biaxial stretching or sequential biaxial stretching, and the film can be produced.

[0044] (Easy adhesion layer) The easy-adhesion layer can be obtained by applying the coating liquid to one or both sides of an unstretched or uniaxially stretched film in the machine direction, drying the film at 75 to 150°C, and stretching the film in one or two directions. The final coating amount of the easy-adhesion layer is 0.05 to 0.20 g / m 2 It is preferable to control the coating amount to 0.05 g / m 2 On the other hand, if the coating amount is 0.20 g / m or more, the adhesiveness is satisfied, which is preferable. 2If it is not more than this, blocking resistance can be obtained, which is preferable.

[0045] Resins used in the easy-adhesion layer include, for example, polyester resins, polyurethane resins, polyester polyurethane resins, polycarbonate polyurethane resins, acrylic resins, etc., and are not particularly limited. Crosslinking agents for the easy-adhesion layer include melamine-based, isocyanate-based, oxazoline-based, and epoxy-based crosslinking agents. Two or more types can also be mixed and used. Due to the nature of in-line coating, these are preferably applied using a water-based coating liquid, and the resins and crosslinking agents are preferably water-soluble or water-dispersible resins or compounds.

[0046] It is preferable to add particles to the easy-adhesion layer to give it easy slipperiness. The average particle size of the fine particles is preferably 2 μm or less. If the average particle size of the particles exceeds 2 μm, the particles are likely to fall off from the easy-adhesion layer. Examples of particles to be contained in the easy-adhesion layer include inorganic particles such as titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silica, alumina, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconia, tungsten oxide, lithium fluoride, and calcium fluoride, and organic polymer particles such as styrene-based, acrylic-based, melamine-based, benzoguanamine-based, and silicone-based particles. These may be added to the easy-adhesion layer alone, or two or more types may be added in combination.

[0047] The coating liquid can be applied by a known method, similar to the coating layer described above, such as reverse roll coating, gravure coating, kiss coating, roll brushing, spray coating, air knife coating, wire bar coating, and pipe doctor coating, which can be used alone or in combination.

[0048] (Hard coat layer) The resin for forming the hard coat layer can be any of (meth)acrylic acid ester, siloxane, inorganic hybrid, urethane acrylate, polyester acrylate, epoxy, etc., without any particular limitation. Two or more kinds of materials can be mixed and used, and particles of inorganic filler or organic filler can be added. Among them, (meth)acrylic acid ester and acrylate resins are preferred, and resins having three or more reactive groups in the molecule as essential components are preferred.

[0049] (Resin having 3 or more reactive groups) Examples of resins having three or more reactive groups include tris[(meth)acryloyloxyalkyl]isocyanurates such as tris(2-acryloyloxyethyl)isocyanurate, tris(3-acryloyloxypropyl)isocyanurate, tris(2-methacryloyloxyethyl)isocyanurate, and tris(3-methacryloyloxypropyl)isocyanurate, as well as trimethylolpropane tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, and propane tri(meth)acrylate. Examples of (meth)acrylates include propionic acid modified dipentaerythritol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propylene oxide modified trimethylolpropane tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, propionic acid modified dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and caprolactone modified dipentaerythritol hexa(meth)acrylate. These may be used alone or in combination of two or more.

[0050] In addition, commercially available hard coat agents can also be used, such as the Beamset (registered trademark) series manufactured by Arakawa Chemical Industries, Ltd., the Aica Itron (registered trademark) series manufactured by Aica Kogyo Co., Ltd., and the Lioduras (registered trademark) series manufactured by Toyo Ink Co., Ltd., without any particular limitations, and can also be used in combination with other (meth)acrylic acid ester compounds.

[0051] (Photopolymerization initiator) When the hard coat layer of the present invention is cured by using ultraviolet light, it is necessary to add a photopolymerization initiator.Specific examples of the photopolymerization initiator include benzophenone, acetophenone, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, benzoin benzoic acid, benzoin methyl benzoate, benzoin dimethyl ketal, 2,4-diethylthioxanthone, 1-hydroxycyclohexyl phenyl ketone, benzyl diphenyl sulfide, tetramethylthiuram monosulfide, azobisisobutyronitrile, benzyl, dibenzyl, diacetyl, β-chloroanthraquinone, (2,4,6-trimethylbenzyldiphenyl)phosphine oxide, and 2-benzothiazole-N,N-diethyldithiocarbamate. In particular, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methylpropan-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, and 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, which are considered to have excellent surface curing properties, are preferred, and among these, 2-hydroxy-2-methyl-1-phenyl-propan-1-one and 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one are particularly preferred. These may be used alone or in combination of two or more.

[0052] The amount of the photopolymerization initiator to be added is not particularly limited. For example, it is preferable to use about 1 to 10% by mass relative to the resin to be used. By adding 1% by mass or more, sufficient curability can be obtained, and by adding 10% by mass or less, the content ratio of the resin having three or more reactive groups is high, and a hard coat film with high crosslink density and high hardness can be obtained.

[0053] (Film thickness) The thickness of the hard coat layer is preferably 1 to 55 μm. If the thickness is more than 1 μm, the hard coat layer is sufficiently cured and a good pencil hardness is obtained. Furthermore, by making the thickness 55 μm or less, curling due to cure shrinkage of the hard coat can be suppressed, and the handling property of the film can be improved.

[0054] (Application method) The hard coat layer can be applied by any method, including Mayer bar, gravure coater, die coater, knife coater, etc., without any particular limitation, and can be appropriately selected according to the viscosity and film thickness. The drying temperature is preferably 60 to 100° C., more preferably 60 to 90° C. If it is 60° C. or higher, sufficient drying can be achieved in a short time, and if it is 100° C. or lower, deformation of the polyester film does not occur, which is preferable.

[0055] (Curing conditions) The hard coat layer can be cured by energy rays such as ultraviolet rays and electron beams, or by heat, but ultraviolet rays and electron beams are preferred in order to reduce damage to the film.

[0056] (UV rays) As the ultraviolet lamp, a high pressure mercury lamp, an electrodeless lamp, etc. can be appropriately selected and used. The cumulative light amount of ultraviolet light is 50 to 500 mJ / cm. 2 is preferable, and 100 to 200 mJ / cm 2 More preferably, 50 mJ / cm 2 If the cumulative light amount is more than 500 mJ / cm, sufficient pencil hardness can be obtained. 2 The following integrated light amount is preferable because it is possible to increase the processing speed and improve the economic efficiency. It is also possible to improve the curing property by irradiating ultraviolet light in an inert gas such as nitrogen, argon, or carbon dioxide, and the amount can be appropriately selected.

[0057] (Electron beam) The electron beam irradiation device may be of area type or scanning type, and may be appropriately selected for use. The cumulative dose of the electron beam is preferably 25 to 500 kGy, more preferably 50 to 300 kGy. If the cumulative dose is 25 kGy or more, sufficient pencil hardness can be obtained, and if it is 500 kGy or less, the processing speed can be increased, which is preferable because it improves economic efficiency. It is preferable to irradiate in an inert gas such as nitrogen or argon with an oxygen concentration of 500 ppm or less. By setting the oxygen concentration to 500 ppm or less, ozone generation can be suppressed, and safety during work can be improved.

[0058] (Pencil hardness) The pencil hardness of the hard coat layer is preferably 2H or more, more preferably 3H or more, and particularly preferably 4H or more. If the hard coat layer has a pencil hardness of 2H or more, it will not easily deform and will not reduce visibility. In general, the harder the hard coat layer has, the higher the pencil hardness is, but it may be 10H or less, 8H or less, or even 6H or less. It can be used without problems in practice.

[0059] (Type of hard coat layer) The hard coat layer in the present invention may have other functions added thereto, so long as it can be used for the purpose of increasing the pencil hardness of the surface and protecting the display as described above.For example, hard coat layers with added functions such as antiglare layers, antiglare antireflection layers, antireflection layers, low reflection layers, and antistatic layers having a certain pencil hardness as described above are also preferably used in the present invention. EXAMPLES

[0060] Next, the effects of the present invention will be described using examples and comparative examples. First, the evaluation methods of the characteristic values ​​used in the present invention will be described below.

[0061] (1) Intrinsic viscosity The film or polyester resin was crushed and dried, and then dissolved in a mixed solvent of phenol / tetrachloroethane = 60 / 40 (mass ratio). After the solution was centrifuged to remove inorganic particles, the flow time of a solution with a concentration of 0.4 (g / dl) at 30°C and the flow time of the solvent alone were measured using an Ubbelohde viscometer, and the intrinsic viscosity was calculated from the time ratio using the Huggins formula and assuming that the Huggins constant is 0.38. In the case of a laminated film, the intrinsic viscosity of each layer alone was evaluated by scraping off the corresponding polyester layer of the film according to the laminate thickness.

[0062] (2) Indentation depth after removing the test force The sample was cut into approximately 2 cm squares and fixed on a micro cover glass 18 x 18 mm (manufactured by Matsunami Glass Co., Ltd.) with an adhesive (Cemedine High Super 30) on the side opposite the measurement side. After adhesion and fixing, it was left at room temperature for 12 hours or more, and then the indentation depth (μm) after removing the test force was measured using a dynamic ultra-micro hardness tester "DUH-211" (manufactured by Shimadzu Corporation) under the following conditions. <Measurement conditions> Test mode: Load-unload test Indenter used: 115 degree ridge angle, triangular pyramid indenter Indenter elastic modulus: 1.140×106N / mm 2 Indenter Poisson's ratio: 0.07 Test force: 50mN Load speed: 4.44mN / sec Load holding time: 2sec Unloading holding time: 0sec

[0063] (3) Plane orientation coefficient ΔP Five samples were taken, and the refractive index in the film longitudinal direction (Nx), width direction (Ny), and thickness direction (Nz) were measured using an Abbe refractometer with sodium D line as a light source according to JIS K7142:1996 5.1 (A method), and the plane orientation coefficient (ΔP) was calculated according to the following formula. The average value of the obtained plane orientation coefficients was taken as the plane orientation coefficient. ΔP=(Nx+Ny) / 2-Nz (4) Pencil hardness According to JIS K 5600-5-4:1999, the measurement was performed with a load of 750g and a speed of 1.0mm / s, and the presence or absence of deformation was visually confirmed. Those without deformation were rated as OK. The measurement was performed five times, and the pencil hardness was recorded as the measured value when four or more were rated as OK.

[0064] (Polymerization of urethane resin) A four-neck flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer was charged with 72.96 parts by mass of 1,3-bis(isocyanate methyl)cyclohexane, 12.60 parts by mass of dimethylolpropionic acid, 11.74 parts by mass of neopentyl glycol, 112.70 parts by mass of polycarbonate diol having a number average molecular weight of 2000, and 85.00 parts by mass of acetonitrile and 5.00 parts by mass of N-methylpyrrolidone as a solvent, and stirred at 75°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Next, the reaction liquid was cooled to 40°C, and then 9.03 parts by mass of triethylamine was added to obtain a polyurethane prepolymer D solution. Next, 450g of water was added to a reaction vessel equipped with a homodisper capable of high-speed stirring, and while stirring and mixing at 25°C, an isocyanate group-terminated prepolymer was added and dispersed in water. Thereafter, acetonitrile and a portion of the water were removed under reduced pressure to prepare a water-soluble polyurethane resin (A) having a solid content of 35 mass %.

[0065] (Polymerization of Water-soluble Carbodiimide Compounds) In a flask equipped with a thermometer, a nitrogen gas inlet tube, a reflux condenser, a dropping funnel, and a stirrer, 200 parts by mass of isophorone diisocyanate and 4 parts by mass of 3-methyl-1-phenyl-2-phospholene-1-oxide as a carbodiimide catalyst were added, and the mixture was stirred for 10 hours at 180°C under a nitrogen atmosphere to obtain isocyanate-terminated isophorone carbodiimide (polymerization degree = 5). Next, 111.2 g of the obtained carbodiimide and 80 g of polyethylene glycol monomethyl ether (molecular weight 400) were reacted at 100°C for 24 hours. Water was gradually added to the mixture at 50°C to obtain a yellow, transparent, water-soluble carbodiimide compound (B) with a solid content of 40% by mass. (Preparation of easy-adhesion layer coating solution)

[0066] The following coating materials were mixed to prepare a coating solution. Water 16.97 parts by mass Isopropanol 21.96 parts by weight Water-soluble polyurethane resin (A) 3.27 parts by mass Water-soluble carbodiimide compound (B) 1.22 parts by mass Particles 0.51 parts by mass (Silica sol with average particle size of 40 nm, solid content concentration of 40% by mass) Surfactant 0.05 parts by weight (Silicone-based, solids concentration 100% by mass)

[0067] (Preparation of Hard Coating Solution 10) 95 parts by weight of pentaerythritol triacrylate (A-TMM-3, manufactured by Shin-Nakamura Chemical Co., Ltd., solids concentration 100%), 5 parts by weight of a photopolymerization initiator (Irgacure (registered trademark) 907, manufactured by BASF Japan, solids concentration 100%), and 0.1 parts by weight of a leveling agent (BYK307, manufactured by BYK Japan, solids concentration 100%) were mixed and diluted with a solvent of toluene / MEK=1 / 1 to prepare a coating solution 10 with a concentration of 40%.

[0068] (Preparation of hard coat coating solution 11) 50 parts by weight of urethane acrylate (Kyoeisha Chemical Co., Ltd., UA-306H, solids concentration 100%), 45 parts by weight of pentaerythritol triacrylate (Shin-Nakamura Chemical Co., Ltd., A-TMM-3, solids concentration 100%), 5 parts by weight of photopolymerization initiator (BASF Japan, Irgacure (registered trademark) 907, solids concentration 100%), and 0.1 parts by weight of leveling agent (BYK Japan, BYK307, solids concentration 100%) were mixed and diluted with a solvent of toluene / MEK=1 / 1 to prepare coating solution 11 with a concentration of 40%.

[0069] (Preparation of polyethylene terephthalate pellets) A continuous esterification reactor consisting of a three-stage complete mixing tank having an agitator, a partial condenser, a raw material inlet, and a product outlet was used as the esterification reactor, and the slurry was continuously fed to the first esterification reactor of the esterification reactor with TPA at 2 tons / hr, EG at 2 moles per mole of TPA, and antimony trioxide at an amount such that Sb atoms were 160 ppm relative to the produced PET, and reacted at normal pressure for an average residence time of 4 hours at 255°C. Next, the reaction product in the first esterification reactor was continuously taken out of the system and fed to the second esterification reactor, and EG distilled from the first esterification reactor was fed to the second esterification reactor at 8% by mass relative to the produced polymer (produced PET), and further, an EG solution containing magnesium acetate in an amount such that Mg atoms were 65 ppm relative to the produced PET and an EG solution containing TMPA in an amount such that P atoms were 20 ppm relative to the produced PET were added, and reacted at normal pressure for an average residence time of 1.5 hours at 260°C. Next, the reaction product in the second esterification reactor was continuously taken out of the system and fed to a third esterification reactor, and an EG solution containing TMPA in an amount such that the P atom was 20 ppm relative to the produced PET was added, and the reaction was carried out at normal pressure for an average residence time of 0.5 hours at 260° C. The esterification reaction product produced in the third esterification reactor was continuously fed to a three-stage continuous polycondensation reactor to carry out polycondensation, and further filtered with a stainless steel sintered filter medium (nominal filtration accuracy of 90% cut of 5 μm particles) to obtain polyethylene terephthalate pellets with an intrinsic viscosity of 0.58 dl / g.

[0070] Example 1 The polyethylene terephthalate pellets were dried under reduced pressure (3 Torr) at 180°C for 8 hours, and then fed to an extruder and melted at 285°C. The polymer was filtered through a stainless steel sintered filter medium (nominal filtration accuracy 10μm particles 95% cut), extruded from a die in the form of a sheet, and then contacted with a casting drum with a surface temperature of 30°C using an electrostatic casting method to cool and solidify, producing an unstretched film. The unstretched film was stretched 3.4 times in the longitudinal direction at 85°C. The easy adhesion layer coating liquid was applied to one side of a PET film by a roll coating method, and then dried at 80°C for 20 seconds. The final (after biaxial stretching) coating amount after drying was 0.06g / m 2 This uniaxially stretched film was stretched 4.3 times in the width direction at 95° C. using a tenter, and then heat-treated at 235° C. for 5 seconds to obtain a polyethylene terephthalate film.

[0071] The hard coat coating solution 10 was applied onto the adhesive layer of the polyethylene terephthalate film using a Mayer bar so that the film thickness after drying would be 5.0 μm, and the coating was dried at 80° C. for 1 minute, followed by irradiation with ultraviolet light (accumulated light amount 200 mJ / cm 2 ). 2 ) to obtain a hard coat film.

[0072] (Examples 2 to 4, Comparative Examples 1 to 3) Except for changing the stretching ratio as shown in Table 1, stretching was performed in the same manner as in Example 1 to obtain polyethylene terephthalate films and hard coat films of Examples 2 to 4 and Comparative Examples 1 to 3.

[0073] (Examples 5 and 6) The polyethylene terephthalate films and hard coat films of Examples 5 and 6 were obtained by stretching in the same manner as in Example 1, except that the thickness was changed as shown in Table 1.

[0074] Example 7 A polyethylene naphthalate film and a hard coat film were obtained by stretching in the same manner as in Example 1, except that polyethylene 2,6-naphthalate (PEN) having an intrinsic viscosity of 0.62 dl / g was used and the stretching ratio was changed.

[0075] (Examples 8 and 9) Using the same polyethylene terephthalate film as in Example 1, and employing the hard coating conditions shown in Table 1, a hard coat film was produced.

[0076] The hard coat film thus prepared was attached to an organic EL module via a 25 μm thick adhesive layer to prepare a flexible display. In each example, the hard coat film was able to protect the organic EL module from external impacts, and good visibility was obtained.

[0077] [Table 1] [Industrial Applicability]

[0078] According to the present invention, a polyester film can be provided that exhibits high surface hardness when a hard coat layer or the like is laminated thereon. A hard coat film having a hard coat layer laminated on the surface of a polyester film of the present invention can be used as a surface protective film for a display such as a flexible display, making it possible to provide a display that is resistant to scratches, impacts, deformation, etc. on the surface of the display and also has excellent design.

Claims

1. A polyester film for use as a protective film for flexible displays, having a crystallinity of 48% or more by the density method and a crystallinity of the film surface of 1.20 or more.

2. A polyester film for protective film of flexible displays as claimed in claim 1, wherein the crystallinity of the film measured by the density method is 65% or less and the crystallinity of the film surface is 3.0 or less.

3. A polyester film for protective film of flexible displays as claimed in claim 1, having an indentation depth of 1.4 μm or less after removing the test force in the film thickness direction, measured using a dynamic ultra-microhardness tester under the following measurement conditions: <Measurement conditions> Test mode: Load-unload test Indenter used: ridge angle 115 degrees, triangular pyramid indenter Indenter elastic modulus: 1.140 x 106 N / mm2 Indenter Poisson's ratio: 0.07 Test force: 50 mN Load speed: 4.44mN / sec Load holding time: 2sec Unloading holding time: 0sec

4. 2. The polyester film for protective films of flexible displays according to claim 1, which has a total light transmittance of 85% or more and a haze of 3% or less.

5. 2. The polyester film for protective films of flexible displays according to claim 1, which has a thickness of 25 to 100 μm and an intrinsic viscosity of 0.50 dl / g or more and 1.00 dl / g or less.

6. 2. The polyester film for protective films of flexible displays according to claim 1, having a plane orientation coefficient ΔP of 0.160 or more.

7. A biaxially oriented polyester film having an easy-adhesion layer on at least one surface of the biaxially oriented polyester film, The polyester film for protective films of flexible displays according to claim 1 , wherein the easy-adhesion layer contains a water-soluble polyurethane resin.

8. The polyester film for protective films of flexible displays according to any one of claims 1 to 7 has a hard coat layer on at least one surface thereof, the hard coat layer contains an acrylate resin having three or more reactive groups in the molecule, A hard coat film for use as a protective film for flexible displays, wherein the pencil hardness of the hard coat layer is 2H or more.

9. A display body using the hard coat film for protective films of flexible displays according to claim 8 as a protective film.

Citation Information

Patent Citations

  • Biaxially oriented polyester film for mold release

    JP2002079574A

  • Polyester film and method for producing the same

    JP2014043571A

  • Polyester film

    JP2014226812A

  • Folding display and mobile terminal device

    JP2018072663A

  • Polyimide resin composition

    JP2016222797A